In vitro assessment, using thrombin generation, of the applicability of prothrombin complex concentrate as an antidote for Rivaroxaban. Issue 6 (3rd July 2013) - Dinkelaar, J.; Molenaar, P. J.; Ninivaggi, M.; de, B.; Brinkman, H. J. M.; Leyte, A.
Summary Background Rivaroxaban has been approved as an antithrombotic agent for prevention of venous thromboembolism with specific indications. At present no antidote is appointed and no guidelines have been formulated for the measurement of Rivaroxaban reversal. Objectives In the present study, we have evaluated the influence of prothrombin complex concentrate (PCC) on the anticoagulant effects of Rivaroxaban as measured by prothrombin time (PT) and thrombin generation tests (TGTs). Methods Plasma and whole blood samples from healthy volunteers were spiked with Rivaroxaban (up to 800 μg L−1) and PCC was added to these samples in concentration ranges as used clinically to reverse the effects of vitamin K antagonists. PT, endogenous thrombin potential (ETP) and calibrated automated thrombography (CAT) assays were performed with varying tissue factor (TF) concentrations. Results Addition of PCC to Rivaroxaban‐spiked samples did not result in normalization of PT and TGT lag time/T‐Lag in ETP and CAT, respectively. In contrast, normalization of ETP and CAT area under the curve did occur. However, the response to PCC addition was strongly TF concentration dependent and in whole blood less PCC was required for Rivaroxaban reversal as compared with plasma. Conclusions Prothrombin complex concentrate does not neutralize the lengthening effect on PT and TGT lag time/T‐Lag of Rivaroxaban anticoagulated blood in vitro; however, total thrombin potential could be normalized. Response of the different TGTs in this respect is assay condition dependent. Therefore, prospective studies are needed to clarify which assay condition and parameter describes in vivo hemostasis best in patients on Rivaroxaban who are treated with PCC.